Thistlefoot - Nethercott, GennaRose (Anchor Books, a division of Penguin Random House LLC, 2022)
"The Yaga siblings--Bellatine, a young woodworker, and Isaac, a wayfaring street performer and con artist--have been estranged since childhood, separated both by resentment and by wide miles of American highway. But when they learn that they are to receive a mysterious inheritance, the siblings are reunited--only to discover that their bequest isn't land or money, but something far stranger: a sentient house on chicken legs. Thistlefoot, as the house is called, has arrived from the Yagas' ancestral home in Russia--but not alone. A sinister figure known only as the Longshadow Man has tracked it to American shores, bearing with him violent secrets from the past: fiery memories that have hidden in Isaac and Bellatine's blood for generations. As the Yaga siblings embark with Thistlefoot on a final cross-country tour of their family's traveling theater show, the Longshadow Man follows in relentless pursuit, seeding destruction in his wake. Ultimately, time, magic, and legacy must collide--erupting in a powerful conflagration to determine who gets to remember the past and craft a new future"--